Penatalaksanaan Fisioterapi Untuk Penderita Cerebral Palsy Spastik Diplegi Di PNTC Karanganyar - Saputri, Oktaviari Dwi, Agus Widodo, S.Fis.,Ftr., M.Fis (2015)
Background: Cerebral Palsy is a disorder of motor child's growth caused by brain damage that occurred in the period before, after, and during birth which is characterized by weakness in the upper limbs, with the characteristics of postural muscle tone is high, especially in the lower extremities. Diplegi is the type of cerebral palsy that affects both legs where the upper limb is lighter than the lower extremities. The problems that arise in this ondition is abnormal muscle tone in the form of spasticity in the lower limbs so that the limitations of functional capabilities such standing and walking.Objective: To investigate the implementation of physiotherapy in cases of spastic cerebral palsy diplegi using such therapy is NDT or Bobath to reduce spasticity through relaxation effect sproduced. Results: After treatment for 6 times the obtained results of the assessment of spasticity with asworth scale T1: Hip 3, 2 ankle, knee 3 to T6: Hip 3, 2 ankle, knee 3. The increase in gross motor skills with GMFM T1: Total score of 27.56 % to T6: 27.58%. Conclusion:The administration of therapy is able to provide relaxation bobath thereby affecting the reduction of spasticity. Exercise with inhibition method approach can improve gross motor skills and abilities activity in patients with spastic cerebral palsy Diplegi.